2010
DOI: 10.1158/0008-5472.can-09-3175
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor Bortezomib Sensitizes Melanoma Cells toward Adoptive CTL Attack

Abstract: Adoptive transfer of tumor-specific cytolytic T lymphocytes (CTL) results in target cell lysis by activating the intrinsic apoptotic cell death program. Not surprisingly, deregulation of the apoptotic machinery is one of the central mechanisms by which tumor cells escape immune destruction despite specific CTL recognition. Here we show that treatment with the proteasome inhibitor bortezomib sensitizes previously resistant tumor cells for cytolytic T-cell attack. Human T cells were redirected toward melanoma ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The systemic treatment of B16 melanoma with bortezomib sensitized B16 melanoma to DC-based immunotherapy, which generated activated CD8 + IFN-g + T lymphocytes (31). Previous research has also indicated that bortezomib may additionally enhance the susceptibility of a variety of formerly apoptosis-resistant tumor cells with dysfunctional mitochondrial apoptotic pathways to the cytolytic action of the treatment-generated CD8 + T lymphocytes (31)(32)(33)(34). A subtoxic concentration of bortezomib was able to drastically favor the mitochondrial apoptotic pathway of melanoma cells by enhancing the release of SMAC and cytochrome c in response to the CTL effector molecules of caspase-8 and cytosolic granzyme B (32).…”
Section: Discussionmentioning
confidence: 99%
“…The systemic treatment of B16 melanoma with bortezomib sensitized B16 melanoma to DC-based immunotherapy, which generated activated CD8 + IFN-g + T lymphocytes (31). Previous research has also indicated that bortezomib may additionally enhance the susceptibility of a variety of formerly apoptosis-resistant tumor cells with dysfunctional mitochondrial apoptotic pathways to the cytolytic action of the treatment-generated CD8 + T lymphocytes (31)(32)(33)(34). A subtoxic concentration of bortezomib was able to drastically favor the mitochondrial apoptotic pathway of melanoma cells by enhancing the release of SMAC and cytochrome c in response to the CTL effector molecules of caspase-8 and cytosolic granzyme B (32).…”
Section: Discussionmentioning
confidence: 99%
“…136 The proteasome inhibitor Bortezomib, which is approved for use in multiple myeloma, sensitizes tumor cells to TRAIL-and NK-mediated cell lysis. 137 Vemurafenib, a specific BRAF inhibitor recently approved for treatment of some melanomas, enhances the expression of several tumor antigens, enabling immune recognition by T lymphocytes. 138 Trastuzumab and cetuximab, monoclonal antibodies directed against tumor-associated receptor TK HER-2 and EGFR, respectively, augment antigen presentation through the formation of immune complexes, leading to stimulation of T-cell-mediated immune responses.…”
Section: Box 1 Immune-based Effects Of Targeted Anticancer Compoundsmentioning
confidence: 99%
“…A combination of the new generation proteasome inhibitor Marizomib with histone deacetylase inhibitors was also tested in preclinical melanoma models, with not yet published results (Potts 2011). Proteasome inhibition also enhanced the effect of cell-mediated immunotherapies in melanoma animal models, such as dendritic cell-based immunization/activation (Schumacher 2006) and adoptive transfer of tumor-specific T lymphocytes (Seeger 2010, Jazirehi 2011. Nevertheless, some paradoxical responses to this type of approach have been observed (Lundqvist 2010).…”
Section: In Vitro and In Vivo Melanoma Preclinical Models About Protementioning
confidence: 99%